IONOMETRIC DETERMINATION OF FLUORINE IN SYNTHETIC FLUORAPATITE AFTER DECOMPOSITION WITH COMPLEXION REAGENT - N. A. Chivireva; O. A. Sakharova; I. V. Stoyanova; A. O. Stoyanov; S. A. Tarasenko; S. V. Toporov (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
It was found that the synthetic fluorapatite (Ca(Sr)10(PO4)6F2), which did not dissolve at the mixture of hydrochloric acid and sodium citrate, fluoride can be determined ionometrically after dissolution in the reagents forming complexes with metal cations and with the F–-ions. It was found that the optimum for the subsequent ionometric determination of fluorine is an approach based on the decomposition of apatites with using ferric(III) chloride solution with subsequent binding Fe(III) in complex with EDTA.